Commensals of underground mammals: European mole (Talpa europaea, Eulipotyphla, Talpidae) and the greater mole-rat (Spalax microphthalmus, Rodentia, Spalacidae) - IRINA STEPANOVA; Alexey Andreychev; RUSLAN KULAKHMETOV; EVGENY LOBACHEV (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Stepanova I, Andreychev A, Kulakhmetov R, Lobachev E. 2021. Commensals of underground mammals: European mole (Talpa europaea, Eulipotyphla, Talpidae) and the greater mole-rat (Spalax microphthalmus, Rodentia, Spalacidae). Biodiversitas 22: 4665-4670. The study of lodgers of burrows of underground mammals was carried out using the method of hunting cylinders (cans). In the study, 29 different representatives from the following classes were identified in the courses of the greater mole-rat and European mole: Diplopoda, Chilopoda, Gastropoda, Insecta, Amphibia, and Mammalia. Among the vertebrates captured are Eurasian common shrew (Sorex araneus), Eurasian pygmy shrew (Sorex minutus), bank vole (Clethrionomys glareolus), common spadefoot toad (Pelobates fuscus), moor frog (Rana arvalis), and common toad (Bufo bufo). Twenty-six different species have been identified among invertebrates. Many animals seek shelter in the burrows of underground mammals from enemies and adverse climatic factors for food or conditions for reproduction. In the central part of Russia, more species of commensals were found in European mole burrows (29) than in greater mole-rat burrows (21).